Outcomes following the delayed management of open tibial fractures. Issue 8 (August 2021) - Higgin, Ryan; Dean, Michael; Qureshi, Amir; Hancock, Nicholas
Highlights: Timely definitive orthoplastic management of open tibial fractures leads to better outcomes. Delayed treatment occurs as a result of deficient infrastructure and patient factors. Little guidance exists for clinicians where delayed definitive management is anticipated. Abstract: Aims: National guidelines set standards for the definitive management of open fractures within 72 h. This study aims to investigate our outcomes where this timeline was unachievable for most cases due to a split-site orthoplastic service. Patients & Methods: 116 consecutive Gustilo-Anderson grade IIIB & IIIC open tibial fractures presenting to our major trauma centre (MTC) between September 2012 and April 2018 were reviewed. The mean follow up was 46 months (17 to 88). 110 (95%) were grade IIIB and 6 (5%) grade IIIC. The most common injury mechanism included road traffic accidents (59%) and falls (28%). Primary outcomes were recorded according to; timing of initial debridement and definitive cover, rates of superficial and deep infection, non-union and amputation. Subgroups were statistically analysed according to time to initial debridement, definitive soft-tissue cover and injury severity score (ISS). Results: The mean time to initial debridement was 11.3 h (2.9 to 38.9) and definitive soft-tissue cover 9.9 days (0 to 37). We recorded rates of: superficial infection; 42 cases (36%), deep infection; 14 cases (12%) and non-union requiring revision; 19 cases (16%). There were 20 amputations (17%) with 9 (8.6%) performed early and 11 (9.5%) delayed. Subgroup analysis showed higher rates of superficial infection (50%, p  = 0.002) and amputation (26.6%, p  = 0.01) for those debrided <12 h. A greater presenting ISS related to a delay to definitive cover >7 days ( p  = 0.05). Primary outcomes trended worse for those covered >7 days but did not reach significance. Conclusion: Major trauma patients are particularly vulnerable to poor outcomes resulting from the delay in definitive management of open fractures. MTC's need resources and a co-located orthoplastic service to achieve national standards and better outcomes. Current guidelines do not advise for the management of patients where a delay in definitive surgery is anticipated.